2004
DOI: 10.1080/03655230410018291
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cervical Paraganglioma: Usefulness of FDG PET Imaging and a Possibility of Rare Origination

Abstract: Cervical paragangliomas are rare tumors derived from neural crest cells. Anatomic imaging techniques rely upon the characteristic spatial relations and the high vascularity of this tumor. Results of computed tomography (CT), magnetic resonance imaging (MRI), and arteriography initially led us to the preoperative diagnosis of cervical paraganglioma. In our case, 2-[18F]-fluoro-2-deoxy-D-glucose positron emission tomography (FDG PET), a type of functional imaging, was also carried out and demonstrated abnormally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It has been previously reported that chromaffin‐tissue‐derived tumours can have an increased uptake of 18 F‐FDG and 18 F‐FDOPA and may be detected by high‐resolution PET imaging 5,9–25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that chromaffin‐tissue‐derived tumours can have an increased uptake of 18 F‐FDG and 18 F‐FDOPA and may be detected by high‐resolution PET imaging 5,9–25 …”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that chromaffin-tissue-derived tumours can have an increased uptake of 18 F-FDG and 18 F-FDOPA and may be detected by high-resolution PET imaging. 5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, to our knowledge 18 F-FDG and 18 F-FDOPA have never been compared directly in the same group of patients. The present study demonstrates that 18 F-FDOPA is a valuable tool in the investigation of such tumours and that 18 F-FDG may provide further information to 18 F-FDOPA in malignant and multicentric chromaffin-tissue-derived tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography CT has been shown to be more sensitive than MRI or plain CT in the detection of metastatic paragangliomas, but not in the detection of localising, non-metastatic paraganglioma, 16 and hence is not recommended as a first-line imaging investigation. Case reports have typically described a mass of increased uptake closely associated with a nerve; 17 better visualisation can be achieved in the case of catecholamine-producing paragangliomas 18 . Angiography has been used to assess the size, location and blood supply of paragangliomas, although they can be adequately assessed with MRI and CT 7 …”
Section: Discussionmentioning
confidence: 99%
“…Metaiodobenzylguanidine (MIBG) scintigraphy is one type of functional imaging that can be used to evaluate multiple or metastatic paragangliomas and paragangliomas in unusual locations. 24,25 Sood et al 26 reported a patient with an occult extra-adrenal para-aortic pheochromocytoma; this tumor was detected by FDG-PET but was missed by other imaging methods. 21 Currently, positron emission tomography (PET) scanning using various radiotracers including 18F-FDG glucose is widely used in oncology.…”
Section: Discussionmentioning
confidence: 99%